Population pharmacokinetics of everolimus in adult liver transplant patients: Comparison to tacrolimus disposition and extrapolation to pediatrics. Issue 11 (14th September 2022) - Itohara, Kotaro; Yano, Ikuko; Nakagawa, Shunsaku; Sugimoto, Mitsuhiro; Hirai, Machiko; Yonezawa, Atsushi; Imai, Satoshi; Nakagawa, Takayuki; Hira, Daiki; Ito, Takashi; Hata, Koichiro; Hatano, Etsuro; et al.
Abstract: Everolimus has recently been used to prevent graft rejection in liver transplantation and reduces the incidence of kidney dysfunction caused by calcineurin inhibitors. In this study, a population pharmacokinetic analysis was conducted to improve the individualization of everolimus therapy. Japanese post‐liver transplant patients whose blood everolimus concentrations were measured between March 2018 and December 2020 were included in this study. A nonlinear mixed‐effect modeling program was used to explore covariates that affect everolimus pharmacokinetics. Individual everolimus pharmacokinetic parameters estimated by the post‐hoc Bayesian analysis using the final model were compared with the tacrolimus dose per trough concentration (D/C) ratio in each patient. The final model was extrapolated to pediatric liver transplant patients for external evaluation. A total of 937 concentrations from 87 adult patients were used in the model‐building process. Everolimus clearance was significantly affected by the estimated glomerular filtration rate, concomitant use of fluconazole, sex, as well as total daily dose of everolimus (TDM effect). The estimated individual apparent clearance of everolimus by the post‐hoc Bayesian analysis was moderately correlated with the D/C ratio of tacrolimus in each patient ( R 2  = 0.330, p  < 0.0001). The estimation accuracy in pediatric patients was considerably high, except for one infant out of 13 patients. In conclusion, population pharmacokinetic analysis clarified several significant covariates for everolimus pharmacokinetics in liver transplant patients. Everolimus pharmacokinetics moderately correlated with tacrolimus pharmacokinetics and could be extrapolated from adult to pediatric patients by body size correction, except for infants.